Post-war Borneo, 1945-1950 : nationalism, empire, and state-building - Ooi, Keat Gin, 1959- (London : Routledge, 2013)
'This book examines Borneo, both British Borneo--Brunei, Sarawak and North Borneo--and Dutch Borneo in the period 1945-50. It discusses the effects of the Japanese surrender, the impact of the subsequent interregnum and Australian and British administrations, the reassertion of Dutch control, the struggle for Indonesian independence, and movements for local autonomy'--Provided by publisher.
Includes bibliographical references (p. [154]-191) and index.
Keywords: Borneo -- Politics and government -- 20th century; Kalimantan (Indonesia) -- Politics and government -- 20th century; Malaysia, East -- Politics and government -- 20th century; Brunei -- Politics and government -- 20th century